2001
DOI: 10.1128/jb.183.2.763-767.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Exhibits Directed Twitching Motility Up Phosphatidylethanolamine Gradients

Abstract: Pseudomonas aeruginosa translocates over solid surfaces by a type IV pilus-dependent form of multicellular motility known as twitching. We wondered whether cells utilize endogenous factors to organize twitching, and we purified from wild-type cells a lipid that caused directed movement. Wild-type P. aeruginosa, but not a pilJ pilus-deficient mutant, showed biased movement up gradients of phosphatidylethanolamine (PE) established in agar. Activity was related to the fatty acid composition of the lipid, as two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 29 publications
(28 reference statements)
3
85
0
1
Order By: Relevance
“…Here we show that the mutation of the WspC homologue in P. putida reduces biofilm formation, which is consistent with the above findings. The chP chemosensory pathway of P. aeruginosa was found to mediate type IV pilibased motility (32)(33)(34). To assess whether CheR3 may potentially be involved in mediating this type of motility, we have thus studied the twitching motility of P. putida KT2440.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we show that the mutation of the WspC homologue in P. putida reduces biofilm formation, which is consistent with the above findings. The chP chemosensory pathway of P. aeruginosa was found to mediate type IV pilibased motility (32)(33)(34). To assess whether CheR3 may potentially be involved in mediating this type of motility, we have thus studied the twitching motility of P. putida KT2440.…”
Section: Discussionmentioning
confidence: 99%
“…The third pathway (wsp) (31) regulates cyclic diguanylate concentrations (formed by the cluster III gene products), which in turn was found to modulate biofilm formation. The fourth pathway, chP (cluster IV genes), modulates the cAMP level (32) and consequently several other features including type IV pili synthesis and twitching motility (33,34). Because the signaling proteins of these pathways are paralogous, there thus exists the possibility of cross-talk between pathways.…”
mentioning
confidence: 99%
“…A second set of che genes revealed by the complete S. meliloti genome sequence (Galibert et al, 2001) is located on the pSymA replicon and linked to genes that control type IV pilus synthesis. Together, the taxis-and pilus-coding genes may have a role in gliding (or twitching) motility (Kearns et al, 2001) appropriate for colonizing the host plant. While it is conceivable that multiple che operons in one cell may interact in a synergistic fashion, the two reported cases rather suggest that these operons specify distinctive sensory pathways operating under diverse and rather specific environmental conditions.…”
Section: Signalling Pathwaysmentioning
confidence: 99%
“…In P. aeruginosa, twitching motility is mediated by type IV pili and is controlled by a complex chemosensory pathway comprised of the proteins PilG, PilH, PilI, PilJ, PilK, ChpA, ChpB, and ChpC (30). Kearns et al (13) had observed that a P. aeruginosa pilJ mutant was deficient in twitching motility and expressed no type IV pili. Therefore, the twitching motility phenotype of the mutants was examined via the subsurface stab assay.…”
mentioning
confidence: 99%